Drought response of water-conserving and non-conserving spring barley cultivars - Appiah, Mercy; Abdulai, Issaka; Schulman, Alan H.; Moshelion, Menachem; Dewi, Elvira S.; Daszkowska-Golec, Agata; Bracho-Mujica, Gennady; Rötter, Reimund P. (Frontiers in Plant Science, 2023)
Breeding barley cultivars adapted to drought requires in-depth knowledge on physiological drought responses. We used a high-throughput functional phenotyping platform to examine the response of four high-yielding European spring barley cultivars to a standardized drought treatment imposed around flowering. Cv. Chanell showed a non-conserving water use behavior with high transpiration and maximum productivity under well-watered conditions, yet rapid transpiration decrease under drought. The poor recovery upon re-irrigation translated to large yield losses. Cv. Baronesse showed the most water-conserving behavior, with the lowest pre-drought transpiration and the most gradual transpiration reduction under drought. Its good recovery (resilience) prevented large yield losses. Cv. Formula was less conserving than cv. Baronesse and produced low, yet stable yields. Cv. RGT’s dynamic water use with high transpiration under ample water supply and moderate transpiration decrease under drought combined with high resilience secured the highest and most stable yields. This dynamic water use behavior combined with higher drought resilience and favorable root traits could potentially create an ideotype for intermediate drought. Prospective studies will examine these results in field experiments and will use the newly gained understanding on water use in barley to improve process descriptions in crop simulation models to support crop model-aided ideotype design.